Characteristics of Immunological Non-Responders in People Living with HIV at Abepura Hospital Papua - Justina Berry Sembiring; Agnes Rengga Indrati; Widya Amalia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Infection of Human Immunodeficiency Virus (HIV) lowers the body's immune system, especially CD4+ cells, making it more susceptible to opportunistic infections. Approximately 10-40% of People Living with HIV/AIDS (PLHIV) fail to achieve normal levels of CD4+ T cells despite continued virological suppression, a condition called Immunological Non-Responders (INR). Previous studies have shown that INR is considered a predictor of disease progression in people with HIV receiving antiretroviral (ARV)s through various mechanisms of suppression of the immune system that increases morbidity and mortality. Papua is an HIV epidemic area with a prevalence of 2.3%. This research is a cohort study conducted at Abepura Hospital from June 2019 to February 2023, which aims to identify the factors that influence the occurrence of INR in PLHIV receiving ARV therapy. There were 123 research subjects consisting of 55 people (44.7%) in the INR group and 68 people (55.3%) in the non-INR group. The results showed that the incidence of INR was higher in males than females (p=0.019), INR was significantly associated with increasing age (p=0.013), and CD4 count was low at the start of ARVs (p=0.002). There was a significant difference in CD4 counts between INR and non-INR (p<0.001). Oral candidiasis as a common opportunistic infection is more common in people with INR than in non-INR. (p=0.037). This study suggested that it is necessary to carry out a CD4 examination at the start of therapy and monitoring every 6 months to detect possible INR to prevent an increased risk of AIDS and non-AIDS, which increases mortality.